PENGARUH PEMBERIAN KOMPOS AMPAS TEBU DAN PUPUK KANDANG TERHADAP PERTUMBUHAN BIBIT STUM MINI KLON PB 260 TANAMAN KARET (Hevea brasiliensis Muell Arg.) - Novendra, Gilang; Amri, Al Ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The Effect of Sludge and Zeolites toward the Growth of PB 260 Clone Rubber Seedlings Mini Stumps. This Research Has Been Conducted In Experimental Garden In The Faculty Of Agriculture, University Of Riau, Bina Widya Campus on Km 12.5 Simpang Baru, Tampan, Pekanbaru City. This Study Was Conducted For 4 Months, Starting From May To August 2017. This research aims to determine the effect of the interaction of the Sludge and Zeolites as well as the main influence and the best treatment for the growth of PB 260 Clone Rubber Seedlings Mini Stumps. This experiment was conducted experimentally using Randomized Complete Random Design (CRD) which consists of 2 factors. The first factor is dosage of Sludge (K) which consists of 3 levels, namely: 0, 100 and 150 G / Plant. The Second Factor Is the Dosage of Zeolites (P) Consisting of 3 Levels, Namely: 0, 25 and 50 / Plant. The data obtained on the observations were analyzed statistically by the analysis of variance. The result of variance analysis is further analyzed by using Duncan’s New Multiple Range Test (DNMRT) at 5%. The results showed that the effect of Sludge gave good result on rubber seeds with dose 150 g / plant. It has effect on high shoots, number of leaves, shoots diameter and widest leaf area. The effect of Zeolites gave good result on rubber seedlings with dose 50 g / plant. It has effect on high shoots, number of leaves, shoots diameter and widest leaf area. Interaction of giving 150 g Sludge / plant and 50 g Zeolites / plant influence on bud diameter and widest leaf area. Keywords: Rubber Seedlings, Sludge, Zeolites, PB 260 Clone Mini Stumps.